Triple therapy in type 2 diabetes; a systematic review and network meta-analysis - Downes, Martin J.; Bettington, Emilie K.; Gunton, Jenny E.; Turkstra, Erika (PeerJ, 2015)
Aims. The purpose was to evaluate the evidence for triple therapy regimen using medicines available in Australia for type 2 diabetes. Methods. A systematic literature review was performed to update the relevant evidence from 2002 to 2014 on triple therapy for type 2 diabetes. A multiple-treatments network meta-analysis was undertaken to summarise the comparative efficacy and harms of different triple therapies. Results. Twenty seven trials were identified, most were six months of duration. The following combinations were included in the network meta-analysis: metformin (MET) + sulfonylureas (SU) (used as reference combination); MET + SU+ dipeptidyl peptidase 4 inhibitors (DPP-4-i); MET + SU+ thiazolidinediones (TZD); MET + SU+ glucagon-like peptide-1 receptor agonists (GLP-1-RA); MET + SU+ insulins; MET + TZD + DPP-4-i; and MET + SU+ sodium/glucose cotransporter 2 inhibitors (SGLT2-i). For HbA1c reduction, all triple therapies were statistically superior to MET+SU dual therapy, except for MET + TZD + DPP-4-i. None of the triple therapy combinations demonstrated differences in HbA1c compared with other triple therapies. MET + SU + SGLT2-i and MET + SU + GLP-1-RA resulted in significantly lower body weight than MET + SU + DPP-4-i, MET+SU+insulin and MET + SU + TZDs; MET + SU + DPP-4-i resulted in significantly lower body weight than MET + SU + insulin and MET + SU + TZD. MET + SU + insulin, MET + SU + TZD and MET + SU + DPP-4-i increased the odds of hypoglycaemia when compared to MET + SU. MET + SU + GLP-1-RA reduced the odds of hypoglycaemia compared to MET + SU + insulin. Conclusion. Care when choosing a triple therapy combination is needed as there is often a risk of increased hypoglycaemia events associated with this regimen and there are very limited data surrounding the long-term effectiveness and safety of combined therapies.
Keywords: Oral antidiabetic drugs; Anti-diabetic medication; Network meta-analysis; Type 2 diabetes; Glycated haemoglobin